STUDENTS’ EXPERIENCES IN FACING ACTUAL LEARNING SITUATIONS IN THE INTERNSHIP PROGRAM - Tombang, Martha; Girik Allo, Markus Deli; Tandikombong, Matius; Baso, Farisha Andi (Publikasi dan UKI Press UKI Toraja., 2024)
This study investigates the experiences of prospective English teachers during their internships, focusing on how they integrate theoretical knowledge into practice and the effects of this experience on their professional development. A quantitative approach was employed, with a survey design to collect data from seventh-semester students of the English Study Program at UKI Toraja who completed their internships during the academic year 2023/2024. The sample consisted of eighteen students selected through purposive sampling due to their relevant classroom experiences. A questionnaire based on a Likert scale was used to capture students’ perceptions and experiences during their internships. The data were tabulated and analyzed using percentage formulas to interpret responses. The findings reveal significant benefits for students, including increased confidence and enhanced teaching skills. However, challenges such as a disconnect between theoretical learning and practical application, inadequate mentor support, and variations in available resources were identified as obstacles to maximizing the internship experience. This research highlights the importance of refining internship programs to better support English language student teachers. Strengthening the connection between academic coursework and practical experiences can lead to more competent and adaptive educators, enriching the overall educational landscape and improving outcomes in teacher training.